Polyurethane-based polymer, preparation method and application thereof, binder and lithium-sulfur battery positive electrode material

By using high ionic conductivity polyurethane-based polymers as binders in lithium-sulfur batteries, the performance problems caused by sulfur insulation and volume expansion of lithium-sulfur batteries are solved, and higher cycling performance and rate performance are achieved.

CN119661805APending Publication Date: 2025-03-21JILIN DONGCHI NEW ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411844400.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Due to the insulation, volume expansion and poor shuttle effects of lithium-sulfur batteries, the commercialization process is hindered, and they face challenges in low utilization, poor rate performance, short cycle life and safety.

Method used

A polyurethane-based polymer is used as a binder, which has high ionic conductivity, and is formed by blending with aqueous polyurethane and poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) to form a hydrogen bond network to improve electrical conductivity and mechanical properties.

Benefits of technology

The polyurethane-based conductive polymer can effectively suppress the shuttle effect, stabilize the battery capacity, improve the circulation and rate performance, improve the insulation of the sulfur positive electrode, promote the rapid transmission of lithium ions and electrons, and improve the discharge specific capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661805A_ABST
    Figure CN119661805A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium-sulfur batteries, and particularly relates to a polyurethane-based polymer, a preparation method and application thereof, an electrode binder and a lithium-sulfur battery positive electrode material. The polyurethane-based polymer provided by the invention has a structure as shown in a formula I; in the formula I, R1 comprises alkylene, substituted alkylene, phenyl, substituted phenyl, naphthyl or substituted naphthyl; r2 comprises an ether group, an alkenyl group, an ester group, a phenolic group, an aldehyde group, a wood fiber group or a glycosyl group. The polyurethane-based conductive polymer provided by the invention has abundant chemical adsorption sites, a hydrogen bond network can be formed among molecules, and soluble lithium polysulfide can be effectively anchored and limited on one side of a positive electrode when the polyurethane-based conductive polymer is used as a positive electrode binder, so that the purposes of inhibiting a shuttle effect, stabilizing the battery capacity and improving the cycle performance are achieved. In addition, the polyurethane-based conductive polymer can greatly eliminate the insulativity of a sulfur positive electrode, promote rapid transmission of lithium ions and electrons and improve the specific discharge capacity. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-sulfur batteries, and in particular relates to a polyurethane-based polymer and a preparation method and application thereof, a binder, and a positive electrode material for a lithium-sulfur battery. Background Art

[0002] Lithium-sulfur (Li-S) batteries have attracted great attention due to their excellent theoretical energy density. In addition, sulfur has the advantages of abundant resources and environmental friendliness. However, due to the insulating properties of sulfur (including S, Li2S2 and Li2S), large volume expansion (~80%) and undesirable "shuttle effect", the commercialization process of lithium-sulfur batteries has always faced multiple challenges in terms of low sulfur utilization, poor rate performance, short long cycle life and safety.

[0003] In order to overcome these problems, people have conducted extensive research on modified positive electrode materials, functional separators, electrolyte additives, and solid or quasi-solid electrolytes. Among them, functionalized binders, as an indispensable component of positive electrode materials, are responsible for firmly adhering elemental sulfur and conductive agents to the current collector to maintain the structural integrity and stability of the electrode. So far, polyvinylidene fluoride (PVDF), a linear polymer with good electrochemical stability and acceptable physical adhesion, is the most commonly used material in lithium-sulfur batteries. Generally speaking, the conductivity of the electrode greatly affects the performance of the battery. The higher the conductivity of the positive electrode, the better the Li + The faster the transmission rate, the better the electrochemical reaction. The PVDF binder is insulating and has no effect on Li + Therefore, designing a functional binder with high ionic conductivity is of great significance to the electrochemical performance of lithium-sulfur batteries. Summary of the invention

[0004] The purpose of the present invention is to provide a polyurethane-based polymer and a preparation method and application thereof, a binder, and a positive electrode material for a lithium-sulfur battery. The polyurethane-based polymer provided by the present invention has high ionic conductivity and excellent performance as an electrode binder.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a polyurethane-based polymer having a structure shown in Formula I:

[0007]

[0008] In formula I, R1 includes an alkylene group, a substituted alkylene group, a phenyl group, a substituted phenyl group, a naphthyl group or a substituted naphthyl group; R2 includes an ether group, an alkenyl group, an ester group, a phenol group, an aldehyde group, a lignocellulosic group or a sugar group; m is an integer of 1 to 100, n is an integer of 6 to 600, and p is an integer of 8 to 10.

[0009] Preferably, the ratio of m to n is 1:1-10;

[0010] The alkylene group and the substituted alkylene group independently have 1 to 10 carbon atoms.

[0011] The present invention also provides a method for preparing the polyurethane-based polymer described in the above technical solution, comprising the following steps:

[0012] mixing waterborne polyurethane, poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) (PEDOT:PSS) and a first organic solvent to obtain the polyurethane-based polymer;

[0013] The polyurethane in the waterborne polyurethane has a structure shown in Formula II:

[0014]

[0015] In formula II, R1 and R2 are the same as those in the above technical solution, and p is 8 to 10;

[0016] The molecular weight of the poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) is 1000 to 10000.

[0017] Preferably, the mass ratio of the waterborne polyurethane to poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) is 1 to 4:1;

[0018] The mixing temperature is 20-80° C. and the mixing time is 1-6 hours.

[0019] Preferably, the preparation method of the waterborne polyurethane comprises the following steps:

[0020] Mixing isocyanate, polyol, polycondensation catalyst and second organic solvent to carry out polycondensation reaction to obtain prepolymer solution;

[0021] Mixing the prepolymer solution and water to obtain the waterborne polyurethane;

[0022] The isocyanate has a structure shown in Formula III:

[0023] O=C=N-R1-N=C=O Formula III;

[0024] The polyol has a structure shown in Formula IV:

[0025]

[0026] In formula IV, z is 20 to 1000.

[0027] Preferably, the isocyanate comprises one or more of isophorone diisocyanate, diphenylmethane-4,4'-diisocyanate, xylylene diisocyanate, 1,6-hexyl diisocyanate, naphthalene-1,5-diisocyanate, methylcyclohexyl diisocyanate, toluene diisocyanate, dicyclohexylmethane diisocyanate, p-phenylene diisocyanate, m-phenylenediisocyanate, 1,3-phenylene diisocyanate, toluene-2,4-diisocyanate, hexamethylene diisocyanate and L-lysine diisocyanate;

[0028] The polyol includes one or more of polyethylene glycol, polytetramethylene glycol, polypropylene glycol, polyhexane adipate, polycarbonate diol and polybutylene adipate;

[0029] The polycondensation catalyst includes one or more of organic tin, antimony glycol and tetrabutyl titanate;

[0030] The temperature of the polycondensation reaction is 40 to 120° C., and the time is 3 to 6 hours.

[0031] The present invention also provides the use of the polyurethane-based polymer described in the above technical solution or the polyurethane-based polymer obtained by the preparation method described in the above technical solution in an adhesive.

[0032] The present invention also provides a binder, which comprises 2-10% of a polyurethane-based polymer and 90-98% of an organic solvent in terms of mass percentage; the polyurethane-based polymer is the polyurethane-based polymer described in the above technical solution.

[0033] The present invention also provides a lithium-sulfur battery positive electrode material, which comprises, by weight percentage, 11-50% conductive carbon, 50-70% sulfur and 1-20% electrode binder; the electrode binder is the binder described in the above technical solution.

[0034] Preferably, the conductive carbon includes conductive carbon 350 and conductive carbon SuperP.

[0035] The present invention provides a polyurethane-based polymer having a structure shown in Formula I; in Formula I, R1 includes an alkylene group, a substituted alkylene group, a phenyl group, a substituted phenyl group, a naphthyl group or a substituted naphthyl group; R2 includes an ether group, an alkenyl group, an ester group, a phenol group, an aldehyde group, a wood fiber group or a sugar group; m is an integer of 1 to 100, n is an integer of 6 to 600, and p is an integer of 8 to 10. The abundant carbamate groups and the sulfonic acid groups of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) in the polyurethane-based conductive polymer provided by the present invention make the polyurethane-based conductive polymer have abundant chemical adsorption sites, and a hydrogen bond network can be formed between the molecules, so that the soluble lithium polysulfide can be effectively anchored and restricted on one side of the positive electrode, so as to achieve the purpose of inhibiting the shuttle effect, stabilizing the battery capacity, and improving the cycle performance and rate performance. In addition, the polyurethane-based conductive polymer provided by the present invention has excellent mechanical properties and conductivity, can strongly bond elemental sulfur and conductive agent while greatly improving the insulation of the sulfur positive electrode, promote the rapid transmission of lithium ions and electrons, and increase the discharge specific capacity, which is very beneficial to the improvement of electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0037] Figure 1 The EIS graph of the sulfur positive electrode in the lithium-sulfur battery obtained in Examples 2 to 4 before cycling;

[0038] Figure 2 The battery cycle diagram of the lithium-sulfur battery obtained in Example 2 and Comparative Example 1 and the SEM image of the sulfur positive electrode after 50 cycles;

[0039] Figure 3 The CV curves of the lithium-sulfur batteries obtained in Example 2 and Comparative Example 1 between 1.6 and 2.8 V are shown;

[0040] Figure 4 The rate performance curve and long cycle curve of the lithium-sulfur battery obtained in Example 2 and Comparative Example 1 are shown;

[0041] Figure 5 The figure is a rate performance curve diagram of the lithium-sulfur battery obtained in Example 6 and Comparative Example 2;

[0042] Figure 6 It is a long cycle curve diagram of the lithium-sulfur battery obtained in Example 6 and Comparative Example 2. DETAILED DESCRIPTION

[0043] The present invention provides a polyurethane-based polymer having a structure shown in Formula I:

[0044]

[0045] In formula I, R1 includes an alkylene group, a substituted alkylene group, a phenyl group, a substituted phenyl group, a naphthyl group or a substituted naphthyl group; R2 includes an ether group, an alkenyl group, an ester group, a phenol group, an aldehyde group, a lignocellulosic group or a sugar group; m is an integer of 1 to 100, n is an integer of 6 to 600, and p is an integer of 8 to 10.

[0046] In the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art.

[0047] In the present invention, R1 includes alkylene, substituted alkylene, phenyl, substituted phenyl, naphthyl or substituted naphthyl. In specific embodiments, it can be alkylene, substituted alkylene, phenyl or substituted phenyl. The number of carbon atoms of the alkylene and substituted alkylene can independently be 1 to 10. In specific embodiments, it can be 3, 5 or 8.

[0048] In the present invention, R2 includes an ether group, an alkenyl group, an ester group, a phenolic group, an aldehyde group, a lignocellulosic group or a sugar group; the ether group includes an alkyl ether group; in a specific embodiment, R2 can be an ethyl ether group, a propyl ether group, a butyl ether group, a hexanediol adipate group or a butanediol adipate group.

[0049] In the present invention, m is an integer of 1 to 100, n is an integer of 6 to 600, and p is an integer of 8 to 10; the ratio of m to n is 1:1 to 10, and in a specific embodiment, it can be 1:6.

[0050] In the present invention, the ratio of the number of carbamate groups, 3,4-ethylenedioxythienyl groups and styrene sulfonic acid groups in the polyurethane-based polymer is 20:1-100:6-600.

[0051] The abundant carbamate groups and sulfonic acid groups of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) in the polyurethane-based conductive polymer provided by the present invention make the polyurethane-based conductive polymer have abundant chemical adsorption sites, and a hydrogen bond network can be formed between molecules, which can effectively anchor and restrict soluble lithium polysulfide on one side of the positive electrode, so as to achieve the purpose of inhibiting the shuttle effect, stabilizing the battery capacity, and improving the cycle performance and rate performance. In addition, the polyurethane-based conductive polymer provided by the present invention has good mechanical properties and conductivity, can greatly improve the insulation of the sulfur positive electrode while firmly bonding the elemental sulfur and the conductive agent, promote the rapid transmission of lithium ions and electrons, and improve the discharge specific capacity, which is very beneficial to the improvement of electrochemical performance.

[0052] The present invention also provides a method for preparing the polyurethane-based polymer described in the above technical solution, comprising the following steps:

[0053] mixing waterborne polyurethane, poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) and a first organic solvent to obtain the polyurethane-based polymer;

[0054] The polyurethane in the waterborne polyurethane has a structure shown in Formula II:

[0055]

[0056] In formula II, R1 and R2 are the same as those in the above technical solution, and p is 8 to 10;

[0057] The molecular weight of the poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) is 1000 to 10000.

[0058] In the present invention, the mass ratio of the waterborne polyurethane to poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) may be 1 to 4:1, and in a specific embodiment, may be 2:1 or 3:1.

[0059] In the present invention, the first organic solvent is one or more of N-methyl-2-pyrrolidone, N,N-dimethylformamide and dimethyl sulfoxide. In a specific embodiment, it can be N-methyl-2-pyrrolidone and / or N,N-dimethylformamide. The mass ratio of the aqueous polyurethane to the volume ratio of the first organic solvent can be 0.01-0.05 g:1-2 mL. In a specific embodiment, it can be 0.03 g:1.5 mL.

[0060] In the present invention, the mixing order of feeding is: mixing the waterborne polyurethane and the first organic solvent, and then adding poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid); the mixing is stirring; the mixing temperature can be 20 to 80°C, and in a specific embodiment, it can be 30°C or 50°C; the mixing time can be 1 to 6 hours, and in a specific embodiment, it can be 2 hours, 4 hours or 5 hours.

[0061] In the present invention, the preparation method of the waterborne polyurethane comprises the following steps:

[0062] Mixing isocyanate, polyol, polycondensation catalyst and second organic solvent to carry out polycondensation reaction to obtain prepolymer solution;

[0063] Mixing the prepolymer solution and water to obtain the waterborne polyurethane;

[0064] The isocyanate has a structure shown in Formula III:

[0065] O=C=N-R1-N=C=O Formula III;

[0066] The polyol has a structure shown in Formula IV:

[0067]

[0068] In formula IV, z is 20 to 1000, and in specific embodiments, can be 50, 100, 300, 500 or 800.

[0069] The invention mixes isocyanate, polyol, polycondensation catalyst and a second organic solvent to carry out polycondensation reaction to obtain a prepolymer solution.

[0070] In the present invention, the isocyanate includes one or more of isophorone diisocyanate, diphenylmethane-4,4'-diisocyanate, xylylene diisocyanate, 1,6-hexamethylene diisocyanate, naphthalene-1,5-diisocyanate, methylcyclohexyl diisocyanate, toluene diisocyanate, dicyclohexylmethane diisocyanate, p-phenylene diisocyanate, m-phenylenediisocyanate, 1,3-phenylene diisocyanate, toluene-2,4-diisocyanate, hexamethylene diisocyanate and L-lysine diisocyanate. In a specific embodiment, it can be one or more of isophorone diisocyanate, diphenylmethane-4,4'-diisocyanate, xylylene diisocyanate, 1,6-hexamethylene diisocyanate, naphthalene-1,5-diisocyanate, methylcyclohexyl diisocyanate, toluene diisocyanate, dicyclohexylmethane diisocyanate, p-phenylene diisocyanate and m-phenylenediisocyanate.

[0071] In the present invention, the polyol includes one or more of polyethylene glycol, polytetramethylene glycol, polypropylene glycol, polyhexane adipate, polycarbonate diol and polybutylene adipate. In a specific embodiment, it can be polyethylene glycol and / or polytetramethylene glycol. The molecular weight of the polyethylene glycol can be 300 to 4000, and in a specific embodiment, it can be 1000. The mass ratio of the isocyanate to the polyol can be 20 to 50:50, and in a specific embodiment, it can be 30:50 or 40:50.

[0072] In the present invention, the polyol is further subjected to a dehydration treatment before the polycondensation reaction; the dehydration treatment is vacuum dehydration; the temperature of the vacuum dehydration can be 80-150°C, and in a specific embodiment, it can be 80°C or 110°C; the time can be 1-5h, and in a specific embodiment, it can be 1.5h or 3.5h; the dehydration treatment also includes adding dimethylpropionic acid; the mass ratio of the polyol to dimethylpropionic acid is 5:1-20:1, and in a specific embodiment, it can be 51.6:4.71; the role of the dimethylpropionic acid is to provide an acidic environment for the polycondensation reaction.

[0073] In the present invention, the polycondensation catalyst includes one or more of organic tin, antimony glycol and tetrabutyl titanate; the organic tin includes dibutyltin dilaurate, dibutyltin dilaurate and / or stannous octoate, and in a specific embodiment, it can be dibutyltin dilaurate; the present invention does not have any special limitation on the amount of the polycondensation catalyst, and the amount familiar to those skilled in the art can be used, and in a specific embodiment, it can be 0.04mL or 0.1mL.

[0074] In the present invention, the second organic solvent is one or more of N-methyl-2-pyrrolidone, N,N-dimethylformamide and dimethyl sulfoxide. In a specific embodiment, it can be N-methyl-2-pyrrolidone and / or N,N-dimethylformamide. The volume ratio of the mass of the isocyanate and the second organic solvent can be 20 to 50 g:4 mL. In a specific embodiment, it can be 31.94:4 mL, 35.96 g:4 mL or 45 g:4 mL.

[0075] In the present invention, the mixing order of feeding is: adding the second organic solvent, isocyanate and polycondensation catalyst to the polyol in sequence.

[0076] In the present invention, the temperature of the polycondensation reaction can be 40-120° C., and in a specific embodiment, can be 80° C. or 100° C.; the time can be 3-6 hours, and in a specific embodiment, can be 4 hours or 5 hours.

[0077] In the present invention, the polycondensation reaction further includes neutralization; the reagent used for the neutralization is an organic base; the organic base includes one or more of triethylamine, ethanolamine and triethanolamine, and in a specific embodiment, it can be triethylamine.

[0078] After obtaining the prepolymer solution, the present invention mixes the prepolymer solution with water to obtain the waterborne polyurethane.

[0079] In the present invention, the solid content of the waterborne polyurethane can be 10-40wt%, and in a specific embodiment, can be 25wt%. The present invention does not have any special restrictions on the amount of water used and the mixing method, as long as the solid content of the waterborne polyurethane can reach the above range.

[0080] The preparation method of the polyurethane-based polymer provided by the present invention is to simply heat and mix polyurethane and PEDOT:PSS to form a hydrogen bond network to synthesize the polyurethane-based conductive polymer. The synthesis steps are simple and the operation is convenient.

[0081] The present invention also provides the use of the polyurethane-based polymer described in the above technical solution or the polyurethane-based polymer obtained by the preparation method described in the above technical solution in an adhesive.

[0082] The present invention also provides a binder, which comprises 2-10% of a polyurethane-based polymer and 90-98% of an organic solvent in terms of mass percentage; the polyurethane-based polymer is the polyurethane-based polymer described in the above technical solution.

[0083] Calculated by mass percentage, the binder provided by the present invention includes 2-10% of the polyurethane-based polymer, and in a specific embodiment, it may be 4%.

[0084] According to the percentage by mass, the binder provided by the present invention comprises 90-98% of an organic solvent, and in a specific embodiment, it can be 96%; the organic solvent is one or more of N-methyl-2-pyrrolidone, N,N-dimethylformamide and dimethyl sulfoxide, and in a specific embodiment, it can be N-methyl-2-pyrrolidone and / or N,N-dimethylformamide.

[0085] The adhesive provided by the invention has good viscosity, good mechanical properties and ionic conductivity.

[0086] The present invention also provides a lithium-sulfur battery positive electrode material, which comprises, by weight percentage, 11-50% conductive carbon, 50-70% sulfur and 1-20% electrode binder; the electrode binder is the binder described in the above technical solution.

[0087] According to the percentage by mass, the lithium-sulfur battery positive electrode material provided by the present invention includes 11-50% of conductive carbon, and in a specific embodiment, it can be 25% or 40%; the conductive carbon includes conductive carbon 350 and conductive carbon SuperP; the mass ratio of the conductive carbon 350 to the conductive carbon SuperP can be 10-30:1-20, and in a specific embodiment, it can be 20:5, 25:5, 20:15 or 25:15.

[0088] Calculated by mass percentage, the lithium-sulfur battery positive electrode material provided by the present invention includes 50-70% sulfur, and in a specific embodiment, it can be 50% or 60%.

[0089] Calculated by mass percentage, the lithium-sulfur battery positive electrode material provided by the present invention includes 1-20% of electrode binder, and in a specific embodiment, it can be 5% or 15%.

[0090] In the present invention, the preparation method of the positive electrode material of the lithium-sulfur battery comprises the following steps:

[0091] The sulfur and part of the conductive carbon are mixed and melt-compounded to obtain a C / S composite material;

[0092] The C / S composite material, the remaining conductive carbon and the binder are mixed to obtain the lithium-sulfur battery positive electrode material.

[0093] In the present invention, the part of the conductive carbon is preferably conductive carbon 350; and the remaining conductive carbon is preferably conductive carbon SuperP.

[0094] In the present invention, the method of mixing the sulfur and part of the conductive carbon is preferably grinding; the grinding time is preferably 10 to 40 minutes, and in a specific embodiment, it can be 30 minutes; the temperature of the melt composite is preferably 120 to 180°C, and in a specific embodiment, it can be 155°C; the time is preferably 18 to 25 hours, and in a specific embodiment, it can be 20 hours; the melt composite is carried out in an inert gas environment, and in a specific embodiment, it can be carried out in an argon environment.

[0095] The lithium-sulfur battery positive electrode material provided by the present invention has abundant polar functional groups and strong electrical conductivity, and the hydrogen bond network therein can better bond the positive electrode material, prevent the positive electrode from collapsing, adsorb polysulfides, and realize the stable cycle of the lithium-sulfur battery.

[0096] In order to further illustrate the present invention, the polyurethane-based polymer provided by the present invention and its preparation method and application, electrode binder, and lithium-sulfur battery positive electrode material are described in detail below in conjunction with the accompanying drawings and examples, but they should not be understood as limiting the scope of protection of the present invention.

[0097] Example 1

[0098] 51.6g of polyethylene glycol (PEG, MW = 1000) was heated at 110°C, stirred, and vacuum dehydrated for 1.5h, then 4.71g of dimethyl propionic acid (DMPA) was added, and the mixture was stirred and dehydrated at 80°C for 3h to obtain a homogeneous mixture. Then, 4mL of N-methyl-2-pyrrolidone (NMP), 31.94g of isophorone diisocyanate (IPDI) and 1 drop of catalyst dibutyltin dilaurate were added in sequence, and triethylamine was added to neutralize the mixture to a pH value of 7 after reacting at 80°C for 3h to terminate the reaction. Subsequently, the prepolymer solution obtained by neutralization was mixed with a certain amount of deionized water to finally obtain a waterborne polyurethane (IWPU) having a solid content of about 25wt%, wherein the molecular weight of the IWPU was between 8000 and 12000.

[0099] One drop of the obtained waterborne polyurethane (IWPU) was added to 1.5 mL of NMP and stirred at room temperature for 6 h. Poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) with a molecular weight of 1000 to 10000 was then added thereto, wherein the mass ratio of IWPU and PEDOT:PSS was 1:1. The mixture was stirred at 40 °C for 3 h to obtain a polyurethane-based polymer (IPUPP) binder.

[0100] Example 2

[0101] Sulfur and conductive carbon (350) were mixed in a mass ratio of 7:3 and ground for 30 minutes, mixed until the color was uniform, and a mixture was obtained. The mixture was transferred into a 100mL polytetrafluoroethylene kettle core and replaced with an argon atmosphere and loaded into the kettle, placed in an oven and heated at a temperature of 155°C for 20 hours to allow sulfur to be compounded with conductive carbon in a molten state. It naturally dropped to room temperature to obtain a C / S composite material, abbreviated as C / S composite. The C / S composite, conductive carbon SuperP and the IPUPP binder prepared in Example 1 were mixed in a mass ratio of 6:3:1 to prepare a sulfur-loaded positive electrode.

[0102] A standard electrolyte of 1,3-dioxolane (DOL) / ethylene glycol dimethyl ether (DME) (1:1, v:v) containing 1 mol / L lithium bistrifluoromethylsulfonyl imide (LiTFSI) and 1 wt% lithium nitrate (LiNO3) was prepared. The above sulfur-loaded positive electrode and lithium metal negative electrode, PP separator, and standard electrolyte were assembled to obtain a lithium-sulfur battery.

[0103] Example 3

[0104] A lithium-sulfur battery was prepared according to the technical solution provided in Example 1, except that the mass ratio of the C / S composite, the conductive carbon SuperP and the IPUPP binder was 7:2:1.

[0105] Example 4

[0106] A lithium-sulfur battery was prepared according to the technical solution provided in Example 1, except that the mass ratio of the C / S composite, the conductive carbon SuperP and the IPUPP binder was 8:1:1.

[0107] Example 5

[0108] 51.6g of polyethylene glycol (PEG, MW = 1000) was heated at 110°C, stirred, and vacuum dehydrated for 1.5h, then 4.71g of dimethyl propionic acid (DMPA) was added, and the mixture was stirred and dehydrated at 80°C for 3h to obtain a homogeneous mixture. Then, 4mL of N-methyl-2-pyrrolidone (NMP), 35.96g of isophorone diisocyanate (IPDI) and 1 drop of catalyst dibutyltin dilaurate were added in sequence, and triethylamine was added to neutralize the mixture to a pH value of 7 after reacting at 80°C for 3h to terminate the reaction. Subsequently, the prepolymer solution obtained by neutralization was mixed with a certain amount of deionized water to finally obtain a waterborne polyurethane (IWPU) having a solid content of about 25wt%, wherein the molecular weight of the IWPU was between 8000 and 12000.

[0109] One drop of the obtained waterborne polyurethane (IWPU) was added to 1.5 mL of NMP and stirred at room temperature for 6 h. Poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) (PEDOT:PSS) with a molecular weight of 1000 to 10000 was then added thereto, wherein the mass ratio of IWPU and PEDOT:PSS was 1:1. The mixture was stirred at 40 °C for 3 h to obtain a polyurethane-based polymer (IPUPP) binder.

[0110] Example 6

[0111] Sulfur and conductive carbon (350) were mixed in a mass ratio of 7:3 and ground for 30 minutes, mixed until the color was uniform, and a mixture was obtained. The mixture was transferred into a 100mL polytetrafluoroethylene kettle core and replaced with an argon atmosphere and loaded into the kettle, placed in an oven and heated at a temperature of 155°C for 12 hours to allow sulfur to be composited with conductive carbon in a molten state. It naturally dropped to room temperature to obtain a C / S composite material, abbreviated as C / S composite. The C / S composite, conductive carbon SuperP and the IPUPP binder prepared in Example 5 were mixed in a mass ratio of 6:3:1 to prepare a sulfur-loaded positive electrode.

[0112] A standard electrolyte of DOL / DME (1:1, v:v) containing 1 mol / L lithium bistrifluoromethylsulfonyl imide (LiTFSI) and 1 wt% lithium nitrate (LiNO3) was prepared. The above sulfur-carrying positive electrode and lithium metal negative electrode, PP separator, and standard electrolyte were assembled to obtain a lithium-sulfur battery.

[0113] Comparative Example 1

[0114] A lithium-sulfur battery was prepared according to the technical solution provided in Example 2, except that the binder was a polyvinylidene fluoride solution.

[0115] Comparative Example 2

[0116] A lithium-sulfur battery was prepared according to the technical solution provided in Example 6, except that the binder was a polyvinylidene fluoride solution.

[0117] Test Example 1

[0118] The electrochemical performance comparison test of the lithium-sulfur batteries obtained in Examples 2 to 4 was carried out, and the EIS spectrum of the sulfur positive electrode before cycling was as follows: Figure 1 The calculated data of ionic conductivity are shown in Table 1.

[0119] Table 1 Ionic conductivity data of sulfur-carrying positive electrodes obtained in Examples 2 to 4

[0120] name Thickness / cm Impedance / Ω <![CDATA[Ionic conductivity / S*cm -1 > IPUPP-631 0.0015 90 <![CDATA[8.5×10 -6 ]]> IPUPP-721 0.0033 50 <![CDATA[3.36×10 -5 ]]> IPUPP-811 0.0018 33 <![CDATA[2.18×10 -4 ]]>

[0121] Depend on Figure 1As can be seen from Table 1, when the mass ratio of the positive electrode C / S composite, conductive carbon Super P and binder (polyvinylidene fluoride solution or polyurethane-based conductive polymer solution) is 8:1:1, the battery with IPUPP@C / S positive electrode has the smallest interface ohmic impedance, the largest ionic conductivity and the fastest reaction kinetics.

[0122] Test Example 2

[0123] The lithium-sulfur batteries obtained in Example 2 and Comparative Example 1 were subjected to current cycle tests. The obtained battery cycle diagram and the SEM photograph of the sulfur positive electrode after the battery was cycled 50 times at a current density of 1C are shown in FIG. Figure 2 As shown, the battery cycle diagrams of using a polyurethane-based conductive polymer binder and a polyvinylidene fluoride binder in a lithium-sulfur battery are (a) and (b), respectively, and the SEM images of the sulfur positive electrode of the battery using a polyurethane-based conductive polymer binder and a polyvinylidene fluoride binder after 50 cycles at a current density of 1C are (c) and (d), respectively.

[0124] Depend on Figure 2 It can be seen that after the battery cycle, the positive electrode of the lithium-sulfur battery using polyvinylidene fluoride (PVDF) as a binder showed serious cracks. In contrast, the positive electrode of the lithium-sulfur battery using a polyurethane-based conductive polymer (IPUPP) as a binder still maintained a relatively uniform surface after 50 cycles, with almost no signs of agglomeration or cracks. This is mainly due to the good self-healing ability of IPUPP, which can alleviate the irreversible damage caused by volume expansion of the sulfur positive electrode during battery cycling. The IPUPP binder plays a key role in maintaining the structural integrity and stability of the sulfur positive electrode during the cycle, thereby improving its electrochemical performance.

[0125] Test Example 3

[0126] The CV curves of the lithium-sulfur batteries obtained in Example 2 and Comparative Example 1 were tested between 1.6 and 2.8 V at a scan rate of 0.1 mV·s -1 , test results see Figure 3 , where the CV curves of the battery using a polyurethane-based conductive polymer binder and a polyvinylidene fluoride binder are (a) and (b), respectively.

[0127] Depend on Figure 3It can be seen that in the negative scan, the battery containing the S@C-IPUPP positive electrode has two reduction peaks at 2.29 and 2.03V, corresponding to the multi-step reduction process; in the positive scan, the lithium-sulfur battery with the S@C-IPUPP positive electrode has a set of overlapping oxidation peaks at 2.34 and 2.40V, corresponding to the oxidation process of Li2S or Li2S2. Compared with the CV curve of the battery containing the S@C-PVDF positive electrode, the battery containing the S@C-IPUPP positive electrode has sharper redox peaks and the potential between the redox peaks is smaller, indicating that in the battery containing the S@C-IPUPP positive electrode, Li + It can move quickly at the interface between the electrode and the electrolyte and can diffuse quickly into the electrolyte, so its redox reaction process is more complete.

[0128] Test Example 4

[0129] The lithium-sulfur batteries obtained in Example 2 and Comparative Example 1 were tested for rate performance and long cycle curve. The test results are shown in Figure 4 , where the rate performance test curve is (a), the long cycle curves at 0.5C and (c) 1C rates are (b), and the long cycle curve at 1C rate is (c).

[0130] Depend on Figure 4 It can be seen that the lithium-sulfur battery with S@C-IPUPP positive electrode has better rate and cycle performance.

[0131] Test Example 5

[0132] The conductivity test of the positive electrode sheet obtained in Example 2 and the positive electrode sheet obtained in Comparative Example 1 was performed using a four-probe method.

[0133] The test results show that the conductivity of the sulfur cathode sheet with polyurethane-based conductive polymer as a binder is 6.58s / cm, which is much higher than the conductivity of the sulfur cathode sheet with polyvinylidene fluoride binder as a binder (0.63s / cm).

[0134] Test Example 6

[0135] The lithium-sulfur batteries obtained in Example 6 and Comparative Example 2 were tested for rate performance. The test results are shown in Figure 5 .

[0136] Depend on Figure 5 It can be seen that the lithium-sulfur battery with S@C-MPUPP positive electrode has better rate performance.

[0137] Test Example 7

[0138] The lithium-sulfur batteries obtained in Example 6 and Comparative Example 2 were subjected to a long cycle curve test at a rate of 1C. The test results are shown in Figure 6 .

[0139] Depend on Figure 6 It can be seen that the lithium-sulfur battery with S@C-MPUPP positive electrode has better cycle stability.

[0140] It can be seen from the above embodiments that the present invention overcomes the main challenges of lithium-sulfur batteries from the positive electrode aspect. By adding a polyurethane-based conductive polymer as the main component of the positive electrode binder, the conductivity of the sulfur positive electrode can be improved, and the rapid transmission of lithium ions and electrons can be promoted. At the same time, it can effectively adsorb polysulfides, which is very beneficial to the improvement of electrochemical performance.

[0141] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A polyurethane-based polymer, characterized in that The polyurethane-based polymer has a structure shown in Formula I: In formula I, R1 includes an alkylene group, a substituted alkylene group, a phenyl group, a substituted phenyl group, a naphthyl group or a substituted naphthyl group; R2 includes an ether group, an alkenyl group, an ester group, a phenol group, an aldehyde group, a lignocellulosic group or a sugar group; m is an integer of 1 to 100, n is an integer of 6 to 600, and p is an integer of 8 to 10.

2. The polyurethane-based polymer according to claim 1, characterized in that The ratio of m to n is 1:1-10; The alkylene group and the substituted alkylene group independently have 1 to 10 carbon atoms.

3. The method for preparing the polyurethane-based polymer according to claim 1 or 2, characterized in that: The following steps are involved: mixing waterborne polyurethane, poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) and a first organic solvent to obtain the polyurethane-based polymer; The polyurethane in the waterborne polyurethane has a structure shown in Formula II: In formula II, R1 and R2 are the same as those in claim 1 or 2, and p is an integer of 8 to 10; The molecular weight of the poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) is 1000 to 10000.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the waterborne polyurethane to poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) is 1 to 4:1; The mixing temperature is 20-80° C. and the mixing time is 1-6 hours.

5. The preparation method according to claim 3, characterized in that: The preparation method of the waterborne polyurethane comprises the following steps: Mixing isocyanate, polyol, polycondensation catalyst and second organic solvent to carry out polycondensation reaction to obtain prepolymer solution; Mixing the prepolymer solution and water to obtain the waterborne polyurethane; The isocyanate has a structure shown in Formula III: The polyol has a structure shown in Formula IV: In formula IV, z is 20 to 1000.

6. The preparation method according to claim 5, characterized in that: The isocyanate includes one or more of isophorone diisocyanate, diphenylmethane-4,4'-diisocyanate, xylylene diisocyanate, 1,6-hexyl diisocyanate, naphthalene-1,5-diisocyanate, methylcyclohexyl diisocyanate, toluene diisocyanate, dicyclohexylmethane diisocyanate, p-phenylene diisocyanate, m-xylylene diisocyanate, 1,3-phenylene diisocyanate, toluene-2,4-diisocyanate, hexamethylene diisocyanate and L-lysine diisocyanate; The polyol includes one or more of polyethylene glycol, polytetramethylene glycol, polypropylene glycol, polyhexane adipate, polycarbonate diol and polybutylene adipate; The polycondensation catalyst includes one or more of organic tin, antimony glycol and tetrabutyl titanate; The temperature of the polycondensation reaction is 40 to 120° C., and the time is 3 to 6 hours.

7. Use of the polyurethane-based polymer according to claim 1 or 2 or the polyurethane-based polymer obtained by the preparation method according to claims 3 to 6 in an adhesive.

8. A binder, characterized in that: Calculated by mass percentage, it comprises 2-10% of a polyurethane-based polymer and 90-98% of an organic solvent; the polyurethane-based polymer is the polyurethane-based polymer according to claim 1 or 2.

9. A positive electrode material for a lithium-sulfur battery, characterized in that: Calculated by mass percentage, it comprises 11-50% conductive carbon, 50-70% sulfur and 1-20% electrode binder; the electrode binder is the binder according to claim 8.

10. The lithium-sulfur battery positive electrode material according to claim 9, characterized in that: The conductive carbon includes conductive carbon 350 and conductive carbon SuperP.

Citation Information

Cited By

  • A rosin-based polyurethane binder, its preparation method, and its application in lithium-sulfur batteries.

    CN122563533A